2009
DOI: 10.1016/j.ejor.2007.12.008
|View full text |Cite
|
Sign up to set email alerts
|

The role of retailer’s performance in optimal wholesale price discount policies

Abstract: The main goal of this paper is to model the effects of wholesale price control on manufacturer's profit, taking explicitly into account the retailer's sales motivation and performance. We consider a stylized distribution channel where a manufacturer sells a single kind of good to a single retailer. Wholesale price discounts are assumed to increase the retailer's motivation thus improving sales. We study the manufacturer's profit maximization problem as an optimal control model where the manufacturer's control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 18 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Hojung and Benton [29] Proposed a model to allow supplier to offer discounts that capitalize on original economic lot sizes and share the buyer's risk of temporary overstocking under uncertain demand. Bykadorov et al [30] Modeled the effect of wholesale price discount on manufacturer's profit and the role of performance of the retailer in deciding optimal policies. Xie et al [31] Analyzed a single manufacturer, multi-retailer chain and studied the effectiveness of price discount in the presence of early order commitment (EOC), and showed that although the EOC based wholesale pricediscount scheme cannot guarantee to reach an optimal solution, it still helps to reduce supply chain cost in comparison to no EOC policy.…”
Section: Nomenclaturementioning
confidence: 99%
“…Hojung and Benton [29] Proposed a model to allow supplier to offer discounts that capitalize on original economic lot sizes and share the buyer's risk of temporary overstocking under uncertain demand. Bykadorov et al [30] Modeled the effect of wholesale price discount on manufacturer's profit and the role of performance of the retailer in deciding optimal policies. Xie et al [31] Analyzed a single manufacturer, multi-retailer chain and studied the effectiveness of price discount in the presence of early order commitment (EOC), and showed that although the EOC based wholesale pricediscount scheme cannot guarantee to reach an optimal solution, it still helps to reduce supply chain cost in comparison to no EOC policy.…”
Section: Nomenclaturementioning
confidence: 99%
“…Pricing. Many researchers have studied the dynamic pricing model on perishable products [22][23][24] and electricity market. Herbon and Khmelnitsky [13] developed an inventory replenishment model with dynamic pricing, considering the interdependence of demand on price and time.…”
Section: Dynamicmentioning
confidence: 99%